2019
DOI: 10.1016/j.jped.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial to change parental practices for drug use in a telehealth prevention program: a pilot study

Abstract: These results demonstrate that the telehealth intervention is effective in modifying the parental practices known to help in preventing drug use. Studies with more number of subjects are required so that the results can be substantiated and generalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…In this study, self-reported parenting practices of adults who are legal guardians of children and adolescents referred to CAPSi due to the use of PAS and/or aggression were compared with self-reported parenting practices of legal guardians of youths with the same population profile but who have never been referred to mental health services. Regarding positive parenting practices, in line with findings from other studies, it was evident that such practices: (a) seem to prevent the manifestation of behavior problems, as pointed out by Bolsoni-Silva and Loureiro (2019) and Borden et al (2014); (b) they may be protective factors against PAS abuse in adolescence, as suggested by Valente et al (2019); (c) and can avoid referral to mental health referral services.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, self-reported parenting practices of adults who are legal guardians of children and adolescents referred to CAPSi due to the use of PAS and/or aggression were compared with self-reported parenting practices of legal guardians of youths with the same population profile but who have never been referred to mental health services. Regarding positive parenting practices, in line with findings from other studies, it was evident that such practices: (a) seem to prevent the manifestation of behavior problems, as pointed out by Bolsoni-Silva and Loureiro (2019) and Borden et al (2014); (b) they may be protective factors against PAS abuse in adolescence, as suggested by Valente et al (2019); (c) and can avoid referral to mental health referral services.…”
Section: Discussionsupporting
confidence: 82%
“…These results indicate that negative parenting practices may be associated with behavioral problems (Bolsoni-Silva et al, 2016;Borden et al, 2014;Campos, 2019;Magnani & Staudt, 2018;Trepat et al, 2014). Such findings reaffirm the indications of Valente et al (2019) that a high frequency of behaviors that characterize an authoritarian style and physical abuse would be associated with the growing vulnerability of adolescents to drug abuse, and neglect should be added as a risk factor.…”
Section: Discussionsupporting
confidence: 73%
“…Thereafter, the number of studies increased with a total of 28 publications between 2018 and 2020. Ten publications were found in 2018 [13,[59][60][61][62][63][64][65][66][67]. The highest proportion of included literature which met the eligibility criteria for…”
Section: Publication Trends/ Timing Of Publicationmentioning
confidence: 99%
“…Participants cut across individuals in the community who were dependent on psychoactive substances and indicated a willingness to quit, oil workers, night club patrons, families, and children and adolescents. Consequently, settings spanned across workplace [75], general population [16,45,46,49,52,[56][57][58][59]66,81,82], health treatment facilities [44,50,51,53,54,60,65,[67][68][69][70][71]76,77,79,80], night clubs [13,64], and schools [55,61,63,[72][73][74]78].…”
Section: Population and Settingsmentioning
confidence: 99%
See 1 more Smart Citation